ALIH KODE DALAM PROSES BELAJAR MENGAJAR EKSPRESI LISAN - SUHARTI, SUHARTI (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract This study is aimed at describing the forms and the reasons of code switching in the Ekspresi Lisan teaching learning process through a naturalistic research. The data were collected by observation and interview. The data were analyzed continually while the data were collected as well as after the data were grouped and categorized. The finding of the research suggests, that there are two forms of code switching in the Ekspresi Lisaan teaching learning process, namely from Javanese to Indonesian and from Jawa krama to Jawa ngoko. There are four reasons of the code switching found in this research. Those reasons are, (1) to express certain intention, (2) to make the topic clearer, (3) to reduce the level of formality in the teaching and learning process, (4) the mastery speech level of the students is not adequate. Keywords: code switching, Javanese speech level